Risk of recurrent overdose associated with prescribing patterns of psychotropic medications after nonfatal overdose - Okumura Y (Dove Medical Press, 2017)
Yasuyuki Okumura,1 Daisuke Nishi21Research Department, Institute for Health Economics and Policy, Association for Health Economics Research and Social Insurance and Welfare, Tokyo, 2Department of Mental Health Policy and Evaluation, National Institute of Mental Health, National Center of Neurology and Psychiatry, Kodaira, JapanObjective: We aimed to estimate risk of recurrent overdose associated with psychosocial assessment by psychiatrists during hospitalization for nonfatal overdose and prescribing patterns of psychotropic medications after discharge. Methods: A retrospective cohort study was conducted using a nationwide claims database in Japan. We classified patients aged 19–64 years hospitalized for nonfatal overdose between October 2012 and September 2013 into two cohorts: 1) those who had consulted a psychiatrist prior to overdose (n=6,790) and 2) those who had not (n=4,950). All patients were followed up from 90 days before overdose until 365 days after discharge. Results: Overall, 15.3% of patients with recent psychiatric treatment had a recurrent overdose within 365 days, compared with 6.0% of those without psychiatric treatment. Psychosocial assessment during hospital admission had no significant effect on subsequent overdose, irrespective of treatment by psychiatrists before overdose. There was a dose–response relationship for the association of benzodiazepine prescription after overdose with subsequent overdose in either cohort, even after accounting for average daily dosage of benzodiazepines before overdose and other confounders. In patients with recent psychiatric treatment, the cumulative proportion of recurrent overdose at 365 days was 27.7% for patients receiving excessive dosages of benzodiazepines, 22.0% for those receiving high dosages, 15.3% for those receiving normal dosages, and 7.6% for those receiving no benzodiazepines. In patients without psychiatric treatment, the cumulative proportion of recurrent overdose at 365 days was 24.3% for patients receiving excessive dosages of benzodiazepines, 18.0% for those receiving high dosages, 9.0% for those receiving normal dosages, and 4.1% for those receiving no benzodiazepines.Conclusion: Lower dose of benzodiazepines after overdose is associated with lower risk of subsequent overdose.Keywords: drug poisoning, self-harm, suicide attempt, repeater, consultation–liaison service, administrative database